On the solution estimation of the first boundary value problem for the quasi-linear systems of differential equations of parabolic type - Savchenko, L. I. (Ukrains’kyi Matematychnyi Zhurnal, 1971)
В статье приводится алгоритм двустороннего приближенного интегрирования первой краевой задачи для квазилинейных систем параболического типа.